2023
DOI: 10.3205/dgkh000433
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy, mode of action and in vivo use of hypochlorous acid (HOCl) for prevention or therapeutic support of infections

Abstract: The objective is to provide a comprehensive overview of the rapidly developing field of the current state of research on in vivo use of hypochlorous acid (HOCl) to aid infection prevention and control, including naso-pharyngeal, alveolar, topical, and systemic HOCl applications. Also, examples are provided of dedicated applications in COVID-19. A brief background of HOCl’s biological and chemical specifics and its physiological role in the innate immune system is provided to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…[1, 17,18] Our finding that the total aerobic count on HCW hands was significantly greater after the ABHR compared with respective baseline counts but was not significantly different to baseline after the novel product suggests that the novel product was more effective at dealing with transient flora acquired during patient care, which is consistent with the higher levels of efficacy achieved by hypochlorous acid than by alcohol in laboratory studies. [19] We sampled the hands of HCW immediately before they undertook hand hygiene and before direct patient care to evaluate contamination levels at baseline. We found that 4% of the 100 baseline samples grew MRSA, and none grew antibiotic-resistant Gram-negative bacteria or C. difficile.…”
Section: Discussionmentioning
confidence: 99%
“…[1, 17,18] Our finding that the total aerobic count on HCW hands was significantly greater after the ABHR compared with respective baseline counts but was not significantly different to baseline after the novel product suggests that the novel product was more effective at dealing with transient flora acquired during patient care, which is consistent with the higher levels of efficacy achieved by hypochlorous acid than by alcohol in laboratory studies. [19] We sampled the hands of HCW immediately before they undertook hand hygiene and before direct patient care to evaluate contamination levels at baseline. We found that 4% of the 100 baseline samples grew MRSA, and none grew antibiotic-resistant Gram-negative bacteria or C. difficile.…”
Section: Discussionmentioning
confidence: 99%
“…HOCl's potent oxidizing capability is acknowledged for its effectiveness in eliminating pathogens. However, it also leads to considerable cellular harm, evidenced by elevated levels of lipid peroxidation, protein oxidation, and DNA damage [11].…”
Section: Hypochlorous Acid (Hocl)mentioning
confidence: 99%